Transcriptome profiling of the initial segment and proximal caput of mouse epididymis - Wang, Xiao; Qiu, Fanyi; Yu, Junjie; Zhou, Meiyang; Zuo, Anjian; Xu, Xiaojiang; Sun, Xiao-Yang; Wang, Zhengpin (Frontiers in Endocrinology, 2023)
Background: The proximal region of the mouse epididymis plays a pivotal role in sperm transport, sperm maturation and male fertility. Several studies have focused on segment-dependent gene expression of the mouse epididymis through high-throughput sequencing without the precision of the microdissection. Methods and Results: Herein, we isolated the initial segment (IS) and proximal caput (P-caput) by physical microdissection using a Lcn9-cre; Rosa26tdTomato mice model. We defined the transcriptome changes of caput epididymis by RNA sequencing (RNA-seq) which identified 1,961 genes that were abundantly expressed in the IS and 1,739 genes that were prominently expressed in the P-caput. In addition, we found that many differentially expressed genes (DEGs) were predominantly or uniquely expressed in the epididymis and region-specific genes were highly associated with transport, secretion, sperm motility, fertilization, and male fertility. Conclusion: Thus, this study provides an RNA-seq resource to identify region-specific genes in the caput epididymis. The epididymal-selective/specific genes are potential targets for male contraception and may provide new insights into understanding segment-specific epididymal microenvironments-mediated sperm transport, maturation, and male fertility.